Human identification and detection through visual processing - Chia, Kian An. (2009)
To identify a person through visual processing, an image capturing device is used to capture a static image of the person before transmitting it to the visual processing system. The system then matches the input against a database of identified images. Facial recognition is a two-dimensional problem whereby its limitations of the processed images are to be taken in frontal view and in fixed lighting conditions. An approach to the problem was to develop a near-real-time face recognition system which extracts the subject’s head before recognizing the person by comparing the characteristics of the face to that of the known individuals. The face images are projected into the feature space “face space”, defined by Eigenfaces, consisting of the eigenvectors of the face, not necessarily corresponding to the isolated features such as eyes, ears, and noses. The framework provides the ability to learn to recognize new faces in an unsupervised manner. Faces are recognized by using the Euclidean distance between the Eigenvectors of the captured image and the known images in the database.